EVALUATION OF LIPID AND THYROID STATUS IN PREGNANCY AND ITS EFFECT ON NEONATAL OUTCOME - gill, gurpreet kaur; Kapila, Diksha (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Maternal nutritional status is essential for the achievement of maternal and fetal growth. Blood lipid concentrations have been associated with adverse pregnancy outcomes such as gestational diabetes, pregnancy-induced hypertension, and high birth weight. As blood lipids are not routinely measured during pregnancy, there is limited information on what is considered normal during pregnancy. In early pregnancy, there is an increase in fat buildup associated with increased fat concentration in blood, lipoprotein, and apolipoprotein in plasma increased significantly during pregnancy. This study was aimed at the analysis of lipid profile and thyroid profile in second- and third-trimester pregnant women, with the incidence of hypertension and their possible effect on neonatal outcome. Methods: Blood samples were collected from the Beri Maternity Hospital, Amritsar, and were analyzed for biochemical investigation, namely lipid profile and thyroid profile. Results: The levels of total cholesterol, triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL), and very LDL have been significantly increased in third-trimester pregnant women as compared to second-trimester pregnant women. However, the level of HDL diminished in the third trimester as compared to the second trimester. Thyroid-stimulating hormone (TSH) levels increased in third-trimester pregnant women. Conclusion: Our findings highlighted the importance of maternal lipid metabolism in preventing pregnancy complications and adverse birth outcomes as human gestation is associated with an “atherogenic” lipid profile which could act as a potential risk factor for pre-eclampsia and endothelial cell dysfunction if further enhanced than the normal limits. Increased blood lipid concentrations during pregnancy are altered by maternal body mass index. This study will help in understanding baseline lipid parameters in the second and third trimesters among pregnant women. Excessive dietary nutrition intake and inadequate physical activity during pregnancy may be important contributors of dyslipidemia which can lead to complications.